Aedes (Ochlerotatus) punctor - Khalin, A. V.; Aibulatov, S. V. (Zenodo, 2021)
Aedes ( Ochlerotatus ) punctor (Kirby, 1837) Northernmost records (Fig. 3e). 69°44 ′ 3.2 ″ N, 32°29 ′ 59.43 ″ E, MP, Pechenga Distr., Rybachiy Peninsula (Sharkov, 1976); 67°29 ′ 16.02 ″ N, 51°52 ′ 52.23 ″ E, NAR, Zapolyarnyy Distr., Kamenka (Monchadsky, 1950); 68°49 ′ 2.6 ″ N, 65°4 ′ 32.98 ″ E, NAR, Zapolyarnyy Distr., Kara, 08.VII.1912 (MOC). Distribution . NWR: AP, Komi, LP, MP, NAR, NP, PP, RK, SPb, VP. Adjacent countries: Norway, Sweden, Finland, Estonia, Latvia, Lithuania and Belarus. Europe (ranging northward to the UK, Belgium, the Netherlands and Denmark); the Holarctic. Published as part of Khalin, A. V. & Aibulatov, S. V., 2021, Northernmost records of mosquito species (Diptera: Culicidae) in northwestern Russia, pp. 46-63 in Zoosystematica Rossica (Zoosyst. Rossica) (Zoosyst. Rossica) 30 (1) on page 56, DOI:10.31610/zsr/2021.30.1.46, http://zenodo.org/record/10124237